Faktor-faktor yang mempengaruhi penggunaan e-pembelajaran di kalangan pelajar tahun akhir fakulti pendidikan, Universiti Teknologi Malaysia - Hassan, Johari (2007)
The International Convention is trying to involve experts from different fields. The cooperation with ministry of education, university and public sectors will produce a strong bond in information sharing particularly on educational technology. Teachers, students and lecturers from inside and outside Malaysia are invited to participate.